Profiling long non-coding RNA changes in silica-induced pulmonary fibrosis in rat. (August 2019) - Sai, Linlin; Yu, Gongchang; Bo, Cunxiang; Zhang, Yu; Du, Zhongjun; Li, Chao; Zhang, Zhenling; Jia, Qiang; Shao, Hua; Peng, Cheng
Highlights: On day 28, lung fibrosis in silica-induced rats was confirmed. Silica induces changes in 682 lncRNAs (300 upregulated, 382 downregulated). The predicted target mRNAs of lncRNAs of silicosis involves in 13 pathways. "Proteoglycans in cancer" signaling pathway in pulmonary fibrosis is valuable to study. LncRNA-miRNA-mRNA ceRNA network may play an important role in pulmonary fibrosis. Abstract: Silicosis is a kind of chronic and incurable lung fibrotic disease with pathogenesis and molecular mechanisms largely unknown. Mounting evidence suggests that long non-coding RNAs (lncRNAs) are involved in the pathogenesis of silicosis. However, how many lncRNAs involved in the pulmonary fibrosis remains to be elucidated. In this study, Wistar rats were exposed to silicon dioxide by an improved tracheal intubation method. Rats in the control group were treated with normal saline solution. Results showed that 28 days after exposure, there were significant differences in body weight and lung coefficient of rats treated with silica compared with control rats. The formation of lung fibrosis in silica-induced rats was confirmed by histologic examination. We then investigated the lncRNAs expression changes in lung tissues of silica-exposed rats and compared that with the rats in the control group using microarray. The results indicated that silica exposure leads to altered expression profile in 682 lncRNAs (300 upregulated and 382 downregulated). Seventy-three ceRNA pairs were acquired by predicted analysis. Kyoto Encyclopedia of Genes and Genomes pathway and Gene Ontology analyses were used to predict the biological pathway and functional classification of lncRNAs. The results showed that silica exposure affected 13 lncRNAs pathways. The functional classification mainly involved in protein binding, cell shape and extracellular exosome. This study indicated that alteration of lncRNAs may play a role in silica-induced pulmonary fibrosis through regulation of expressions of functional genes in lungs of rat. Our results provide more insights into the mechanism of silicosis.